2013
DOI: 10.1159/000348844
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel GATA6 Mutations Cause Childhood-Onset Diabetes Mellitus, Pancreas Malformation and Congenital Heart Disease

Abstract: Background:GATA6 mutations are the most frequent cause of pancreatic agenesis and diabetes in human sporadic cases. In families, dominantly inherited mutations show a variable phenotype also in terms of endocrine and exocrine pancreatic disease. We report two novel GATA6 mutations in an independent cohort of 8 children with pancreas aplasia or hypoplasia and diabetes. Methods: We sequenced GATA6 in 8 children with diabetes and inborn pancreas abnormalities, i.e. hypoplasia or aplasia in which other known candi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…The majority of GATA6 mutations in these individuals were de novo heterozygous mutations. Subsequent work confirmed this finding and revealed a more complex picture . First, patients with GATA6 mutations often present defects in other organs including the heart and gut.…”
Section: Mutations In Gata Factors and Pancreas Abnormalities In Humansmentioning
confidence: 78%
See 1 more Smart Citation
“…The majority of GATA6 mutations in these individuals were de novo heterozygous mutations. Subsequent work confirmed this finding and revealed a more complex picture . First, patients with GATA6 mutations often present defects in other organs including the heart and gut.…”
Section: Mutations In Gata Factors and Pancreas Abnormalities In Humansmentioning
confidence: 78%
“…Subsequent work confirmed this finding and revealed a more complex picture. [25][26][27][28][29][30][31][32][33][34] First, patients with GATA6 mutations often present defects in other organs including the heart and gut. Second, patients with GATA6inactivating mutations show a broad spectrum of pancreatic abnormalities, from complete agenesis of the pancreas to moderate diabetes developed during adulthood with or without exocrine insufficiency (that might be suggestive of some degree of acinar function defects).…”
Section: Mutations In Gata Factors and Pancreas Abnormalities In Humentioning
confidence: 99%
“…Consequently, these patients suffer from severe exocrine pancreatic insufficiency and neonatal diabetes due to the absence of insulin-secreting endocrine β cells. Further studies have identified heterozygous GATA6 patients with a wide spectrum of phenotypes ranging from non-diabetic, mildly diabetic in adults, to severely diabetic with no pancreas in newborns, and marked phenotypic variability is observed even among affected members of the same family (Bonnefond et al, 2012; Catli et al, 2013; Chao et al, 2015; De Franco et al, 2013; Eifes et al, 2013; Gong et al, 2013; Stanescu et al, 2015; Suzuki et al, 2014; Yorifuji et al, 2012; Yu et al, 2014). However, as with other cases of haploinsufficient disease genes, inactivation of one Gata6 allele does not cause apparent defects in mice (Morrisey et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac malformations are present in all cases of GATA6 mutations reported to date (4), whereas it appears that the pancreatic defect is variable and neonatal diabetes is not present in all affected patients (5)(6)(7)(8). Children carrying mutations in GATA6 were also found to have other endocrine anomalies (pituitary agenesis and hypothyroidism), gastrointestinal malformations (intestinal malrotation, microcolon, gallbladder agenesis, biliary atresia, and proctorrhagia), bicornuate uterus, neurodevelopmental anomalies, and seizures (1,5,(8)(9)(10). The frequency of these manifestations varies and there appears to be no correlation between the position of the mutation and a specific phenotype.…”
mentioning
confidence: 99%